STRATEGI PEMBELAJARAN BAHASA ARAB DALAM MENINGKATKAN MINAT BERKOMUNIKASI BAHASA ARAB DI KELAS 3 MTs PUTRI DARUNNAJAH 2 CIPINING - A Savana Na’ilah Saty; Mahmun Mahmun; Nailil Muna Sholihah; M. Yogi Saputra (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Arabic is a necessity that must be learned by grade 3 students at MTs Putri Darunnajah 2 Cipining Bogor, with various strategies in learning methods that are conveyed by teachers to students in class to achieve appropriate student knowledge standards in learning Arabic.The method used in this research is a qualitative descriptive method. The informants in this research were the school principal, Arabic teachers and students. Data collection techniques use observation, interviews and documentation. Test the validity of the data with triangulation.The results of the research show that: Arabic language learning strategies using various unique methods must be presented by teachers in the teaching process. There are supporting factors found in this, including students' familiarization with Arabic pronunciation and the use of Dhomir in accordance with correct Arabic language rules and the atmosphere in the classroom. The importance of supporting students' interest in learning Arabic is the beginning of the process of forming students' understanding of Arabic.